2015
DOI: 10.1371/journal.pone.0140778
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anterior Nuclei of the Thalamus: A Subcortical Gate in Memory Processing: An Intracerebral Recording Study

Abstract: ObjectiveTo study the involvement of the anterior nuclei of the thalamus (ANT) as compared to the involvement of the hippocampus in the processes of encoding and recognition during visual and verbal memory tasks.MethodsWe studied intracerebral recordings in patients with pharmacoresistent epilepsy who underwent deep brain stimulation (DBS) of the ANT with depth electrodes implanted bilaterally in the ANT and compared the results with epilepsy surgery candidates with depth electrodes implanted bilaterally in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 41 publications
(44 reference statements)
5
22
1
Order By: Relevance
“…These findings are in line with previous studies showing higher white matter connection strength among cortical-subcortical networks in MDD [Long et al, 2015] and GM alteration in related regions Wise et al, 2016]. The neocortex-striatum-thalamus-cerebellum circuitry may contribute to altered regulation of emotion and cognition in mood disorders [Bostan et al, 2013;Buckner, 2013;Guo et al, 2015;Price and Drevets, 2012], while the thalamohippocampal circuitry might be more specifically related to memory disturbances in depression [Price and Drevets, 2009;Stillova et al, 2015]. The neocortex-striatum-thalamus-cerebellum circuitry may contribute to altered regulation of emotion and cognition in mood disorders [Bostan et al, 2013;Buckner, 2013;Guo et al, 2015;Price and Drevets, 2012], while the thalamohippocampal circuitry might be more specifically related to memory disturbances in depression [Price and Drevets, 2009;Stillova et al, 2015].…”
Section: Mdd-related Alterations In Morphological Connectivitysupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are in line with previous studies showing higher white matter connection strength among cortical-subcortical networks in MDD [Long et al, 2015] and GM alteration in related regions Wise et al, 2016]. The neocortex-striatum-thalamus-cerebellum circuitry may contribute to altered regulation of emotion and cognition in mood disorders [Bostan et al, 2013;Buckner, 2013;Guo et al, 2015;Price and Drevets, 2012], while the thalamohippocampal circuitry might be more specifically related to memory disturbances in depression [Price and Drevets, 2009;Stillova et al, 2015]. The neocortex-striatum-thalamus-cerebellum circuitry may contribute to altered regulation of emotion and cognition in mood disorders [Bostan et al, 2013;Buckner, 2013;Guo et al, 2015;Price and Drevets, 2012], while the thalamohippocampal circuitry might be more specifically related to memory disturbances in depression [Price and Drevets, 2009;Stillova et al, 2015].…”
Section: Mdd-related Alterations In Morphological Connectivitysupporting
confidence: 91%
“…Thalamocortical functional dysconnectivity was also observed in psychotic disorders and related to cognitive impairment [Lui et al, 2014;Woodward and Heckers, 2015]. The neocortex-striatum-thalamus-cerebellum circuitry may contribute to altered regulation of emotion and cognition in mood disorders [Bostan et al, 2013;Buckner, 2013;Guo et al, 2015;Price and Drevets, 2012], while the thalamohippocampal circuitry might be more specifically related to memory disturbances in depression [Price and Drevets, 2009;Stillova et al, 2015].…”
Section: Mdd-related Alterations In Morphological Connectivitymentioning
confidence: 99%
“…These regions have been associated with attentional processing, an important element of memory encoding [16,17,21]. We also found a negative correlation between the volume of white matter of several subcortical structures and the performance in this task, in line with recent studies showing the involvement of subcortical structures in memory functioning [86][87][88]. Finally, the volume of grey matter of the rolandic operculum and the fusiform gyrus were associated with PAL performance in accordance with the role of these structures in somatosensory processing [12,13,18,89].…”
Section: Discussionsupporting
confidence: 90%
“…The motivation for studying the ANT stems from preclinical studies that demonstrated its ability to regulate seizure onset and propagation in mesial temporal lobe seizure, thereby potentially making ANT a clinically relevant target in TLE . Furthermore, the ANT is integral to the limbic circuit that regulates neurobehavioral functions, including memory, mood, and emotions . It has been shown that open‐loop deep brain stimulation (DBS) of ANT can disrupt these physiological processes and worsen sleep, depression, and memory .…”
Section: Discussionmentioning
confidence: 99%